(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate the effectiveness of distance learning Lean Six Sigma training using the Método CPA. The search for distance learning has increased at an exponentially never seen speed, due to the recent pandemic events. In this sense, there is a reaction from educational institutions seeking to meet this demand. These institutions seek to meet students’ expectations, train them for the corporate world and compete equally in the market. The subject becomes pertinent to our reality as more students opt for this type of teaching. Mainly seeking versatility in teaching time and physical location, efficiency in learning and practical application in companies of the concepts learned in classes. The development of this research will give us an insight into distance learning and its necessary immersion in society, which is not fully defined. In this way, online Lean Six Sigma Black Belt training will be presented through the company Método CPA. This training is considered a professional course, not falling within technical education, undergraduate or postgraduate studies, therefore it does not require accreditation and supervision from the MEC (Ministry of Education). We will follow all the content of the Lean Six Sigma Black Belt training, its practical relevance within companies and its results with its students, thus positioning ourselves in a general way on this topic. The expected result is to share the training structure to contextualize the research field, demonstrate the results, student evaluation data and completion time, identify coherences and divergences, obtain practical professional results from the application of the Lean Six Sigma methodology and finally contribute to the improvement of distance training in educational institutions.